Research ethics: Overcoming the exploitative dynamic through ethical research (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Research ethics is a framework of principles and guidelines designed to ensure that scientific inquiry protects participants’ rights and welfare while upholding integrity. Core principles includes respect for persons, beneficence, and justice which govern all research stages. Respect for persons requires informed consent, confidentiality, and additional safeguards for individuals with diminished autonomy. Beneficence involves maximizing benefits and minimizing harm. Justice demands equitable distribution of both research burdens and benefits. Despite these safeguards, exploitative dynamics persist when power imbalances enable researchers to pursue agendas at the expense of marginalized communities. Such dynamics manifest as tokenistic participation, extractive “helicopter” research, lack of reciprocity, disregard for local context, and unaddressed harms, all of which erode trust and compromise research validity. Mitigating these issues for ensuring ethical research requires proactive strategies at both the investigator and institutional levels. Researchers should co-design studies with community partners, implement participant-centered informed consent, ensure fair recruitment, prioritize participant welfare, establish benefit-sharing agreements, and maintain transparency and accountability. Academic institutions must bolster ethics infrastructures — streamlining review processes, providing ongoing ethics training, facilitating genuine community engagement, and fostering a culture that rewards ethical conduct. By embedding these measures into research design and oversight, the research community can prevent exploitation, honour participants’ dignity, and advance knowledge in an equitable manner. Upholding rigorous ethical standards not only safeguards scientific credibility but also builds public trust and contributes to a more just and inclusive society.